2007
DOI: 10.1002/dneu.20591
|View full text |Cite
|
Sign up to set email alerts
|

α‐Phenyl‐n‐tert‐butyl‐nitrone reduces lipopolysaccharide‐induced white matter injury in the neonatal rat brain

Abstract: Lipopolysaccharide (LPS)-induced white matter injury in the neonatal rat brain is at least partially associated with oxidative stress. alpha-Phenyl-n-tert-butyl-nitrone (PBN) (100 mg/kg) significantly attenuated LPS (1 mg/kg)-induced brain injury, as indicated by the reduction in bilateral ventricular enlargement, apoptotic cell death of oligodendrocytes (OLs), and the loss of OL immunoreactivity in the neonatal rat brain. Protection of PBN was linked with the attenuated oxidative stress induced by LPS, as ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 40 publications
7
48
0
2
Order By: Relevance
“…In the current study, systemic LPS exposure resulted in nitrosative and oxidative damage similar to that induced by i.c. LPS injection, as reported previously (Fan et al, 2008b, Fan et al, 2008c). Increased expression of NT (Figs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the current study, systemic LPS exposure resulted in nitrosative and oxidative damage similar to that induced by i.c. LPS injection, as reported previously (Fan et al, 2008b, Fan et al, 2008c). Increased expression of NT (Figs.…”
Section: Resultsmentioning
confidence: 95%
“…Our previous studies have shown that neonatal exposure (postnatal day 5, P5) to lipopolysaccharide (LPS) through an intracerebral (i.c.) injection results in brain inflammation and white matter and neuronal injury in rats, which was closely associated with the increased nitrosative and oxidative stress following LPS exposure (Fan et al, 2008b, Fan et al, 2008c). The inflammatory response that ensues because of the initial occult exogenous oxidative/nitrosative stress becomes a secondary endogenous source of reactive oxygen species (ROS) and reactive nitrogen species (RNS).…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, other factors may influence the response to rHI that include complex systemic illness, nutritional, metabolic, endocrine, genetic and epigenetic factors. Postnatal infection is an important risk factor for WMI [52]–[54], and a number of inflammatory factors have been shown to cause WMI and promote preOL degeneration [55][57]. Recurrent postnatal infections, which may predispose to rHI, are associated with increased risk for progressive WMI in human preterm survivors [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, current data indicate that redox dysregulation contributes to myelination impairment due to early-life inflammation. Alpha-phenyl-n-tert-butyl-nitrone (PBN), a free radical scavenger, protects oligodendrocytes and myelination against neonatal immune challenge (Fan et al, 2008). Likewise, NAC prevents this deficit by attenuating the dysfunction of peroxisomes, organelles important for ROS detoxification and myelin-lipid metabolism (Paintlia et al, 2008).…”
Section: Oligodendrocytes/myelinationmentioning
confidence: 99%